1925
DOI: 10.1051/jphysrad:01925006010100
|View full text |Cite
|
Sign up to set email alerts
|

Sur la théorie de l'électrostriction dans les liquides isolants

Abstract: Sommaire. 2014 Un liquide isolant, soumis à un champ électrique uniforme, subit en général une contraction appelée électrostriction. L'équilibre atteint n'est pas le même suivant que l'opération est isotherme ou adiabatique. Ce dernier cas semble réalisé quand on charge le condensateur dans une fraction de millième de seconde, par exemple. Dans l'un et l'autre cas, un calcul thermodynamique donne très simplemeril 1 la contraction 0 3 B 8 subie par l'unité de volume en utilisant la fonction caractéristiquc rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1933
1933
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…β was determined by comparing the free energies from Equation (32) and from the literature [18], and minimizing the sum of the squares of the errors between the two energies my iteratively adjusting the 4 β parameter. The energies were compared for a deformation range of 1 1.02 λ ≤ < and an applied electric field of 1 E GV =…”
Section: Axial Elongation With Applied Electric Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…β was determined by comparing the free energies from Equation (32) and from the literature [18], and minimizing the sum of the squares of the errors between the two energies my iteratively adjusting the 4 β parameter. The energies were compared for a deformation range of 1 1.02 λ ≤ < and an applied electric field of 1 E GV =…”
Section: Axial Elongation With Applied Electric Fieldmentioning
confidence: 99%
“…In the late 19 th century and the early part of the 20 th century, several studies reported a relationship between the applied electric field, stress field, and strain field for cylindrical condensers [24][25][26][27][28][29][30][31][32][33]. In the middle portion of the 20 th century, many scholars studied the broader applications of electrostrictive materials, and established more specific definitions of electrostrictive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in this problem is shown by the large number of optical studies (e.g. Bruhat & Grivet, 1935;Konstantinova, Ivanov & Grechushnikov, 1969;Rogers, 1977;Kobayashi, Takahashi, Hosokawa & Uesu, 1978;Horinaka, Tomii, Sonomura & Miyauchi, 1985;Kobayashi, Asahi & Takahashi, 1987) of this crystal. However, it seems that crucial assessments of the accuracies of the published results have not been made, presumably because of a lack of knowledge of the possible systematic errors.…”
Section: Introductionmentioning
confidence: 99%